Retinal Microvascular Density and Perfusion during an Insulin-Induced Hypoglycemia Episode: A Warning Call - Gerardo González-Saldivar; José Gerardo González-González; David Robert Chow; Jesús Mohamed-Hamsho; Jesús Hernan González-Cortés; Adriana Sánchez-García; René Rodríguez-Gutiérrez (International Journal of Clinical Practice)
Aim. To evaluate retinal vascular perfusion and density by optical coherence tomography angiography (OCTA) before, during, and after hypoglycemia in individuals with diabetes mellitus with or without diabetic retinopathy (DR). Methods. A focused clinical history was performed, followed by an ophthalmological examination to document retinopathy status. OCTA was performed at baseline, at hypoglycemia, and at glucose normalization. Eye tracking and eye alignment devices on the platform were used to obtain a macular thickness cube (512 × 128) and vascular perfusion and density protocols of 3 × 3 mm. Retinal vascular reactivity was analyzed with superficial plexus vascular perfusion and density protocols on OCTA. Results. Fifty-two participants encompassing 97 eyes fulfilled the eligibility criteria. Their mean age was 42.9 ± 15.1 years (range, 22 to 65), and 20 (38.2%) were men. We found a statistically significant difference in vascular perfusion and density when comparing all groups at baseline. The controls had higher vascular perfusion and density values than the cases. Vascular perfusion and density were significantly reduced in all groups during the hypoglycemia episode, except for vascular density in DR cases. Conclusion. Acute hypoglycemia significantly alters the retinal vascularity in DM patients with and without DR, suggesting that repeated episodes of acute hypoglycemia could exacerbate retinopathy in the long term.